Lessons on policy transfer the Philippine experience - Baylon, Minerva S. (2014)
The article looks into how globalization has taken on forms that tend to challenge the internal governance of countries. One such form is referred to as policy transfer, defined as a "process by which knowledge of policies, administrative arrangements, institutions and ideas in one political system (past or present) is used in the development of similar features in another."Deregulation and liberalization is an example of policy transfer. Although some literature on the subject matter highlight its positive aspect, that of lesson drawing, other researchers point out the constraint posed by incompatible political systems and differences in the contexts on the success of such a policy transfer. In the Philippines, deregulation is a conditionality imposed by donor countries and international organizations. A case study of the formulation of the Electric Power Industry Reform Act of ERIPA further illustrates how pressure and influence from the international financial institutions and other international organizations, as agents of policy transfer, determined the final shape of the policy. This study is an addition to the body of literature that lends support to conceptual and empirical researchers advocating the importance of taking into account the political and administrative, socioeconomic and cultural contexts of policy transfer. It also shows how policy transfer can challenge the independence and integrity of institutions like the legislature and executive branches of government.
Keywords: Deregulation; Electric Power Industry Reform Act (EPIRA); Deregulation of electric utilities; Energy industry laws